The impact of family planning on maternal mortality in Indonesia: what future contribution can be expected? - Budi Utomo; Purwa Kurnia Sucahya; Nohan Arum Romadlona; Annette Sachs Robertson; Riznawaty Imma Aryanty; Robert Joseph Magnani (BMC, 2021)
Abstract Background Although efforts to reduce high maternal mortality in countries such as Indonesia tend to focus on addressing health risks among pregnant women, family planning has been shown globally to reduce maternal mortality by reducing both total and higher-risk pregnancies. This article assesses past contributions of family planning to the reduction of maternal mortality in Indonesia and the potential future contribution toward achieving the 2030 SDG maternal mortality goal. Methods The study takes advantage of data from long series of population censuses and large-scale surveys that are available in few other low- and middle-income countries. We use the decomposition method suggested by (Matern Child Health J, 16:456-463, 2012) and regression-based policy simulations to estimate the number of maternal deaths averted during 1970-2017 due to contraceptive use and project potential future contributions to the year 2030. Results It is estimated that between 523,885 and 663,146 maternal deaths were averted from 1970 to 2017 due to contraceptive use, a 37.5-43.1% reduction. If the contraceptive prevalence rate (CPR) were to rise from 63% in 2017 to 70% in 2030 and unmet need for family planning were to fall to from 10 to 7%, an additional 34,621-37,186 maternal deaths would be averted, an 18.9-20.0% reduction. A 2030 CPR of 75% and unmet need for family planning of 5% would result in 51,971-54,536 maternal deaths being averted, a 28.4-29.4% reduction. However, the CPR growth rate would have to nearly double the 2000-2017 rate to reach 70% CPR by 2030 and more than triple to reach 75%. Achieving the most ambitious target would still leave the maternal mortality ratio at 125 in 2030 without corresponding improvements in maternal health services. Conclusions Although substantial reductions in maternal mortality between 1970 and 2017 can be attributed to contraceptive use and further contributions to the year 2030 are probable, smaller contributions are likely due to the already relatively high CPR and the challenges that must be overcome to move the CPR significantly higher. The ability of Indonesia to reach the 2030 SDG maternal mortality target of 70 maternal deaths per 100,000 live births will depend primarily upon health system effectiveness in addressing health risks to women once they are pregnant.